Fuentes de financiamiento y gestión logística en comerciantes del mercado Modelo ciudad de Iquitos año 2022 - Quiroz Arista, Grace (2022)
The present investigation set as a general objective to identify the presence of financing and logistics management in the merchants of the Iquitos city model market in 2022, characterizing the most relevant aspects in the study population considering that financing is vital for business development and these usually come from formal and informal credit, which is a consequence of informality, ignorance and the level of access, among others, an also important aspect is the logistics management of businesses which have not received training in this regard and present problems such as the presence of inadequate and untimely logistics processes, among others, for this reason an investigation was proposed with a quantitative, descriptive approach and a non-experimental cross-sectional design that included 79 merchants as a study sample, identifying that merchants resort to a greater extent to informal financing than formal, that the fi Financing presents as characteristics high costs, that the level of access is medium, that the majority of merchants prefer credits of less than one year, and that the destination of financing is used mainly for the purchase of merchandise and equipment, insofar as logistics management presents positive aspects such as action planning, cost analysis and storage in most participants, as well as problems of inadequate distribution channels, lack of control and availability of equipment, considering that good logistics management would represent high costs for your business however, it would also represent higher income due to the reduction in losses.